TERRORISM PREVENTION WITH INTELLIGENCE-LED POLICING AND PREDICTIVE POLICING COLLABORATION IN SOUTH SUMATERA REGION - Marzuki Ismail; Ade Mulya; Suardi Jumaing; Bayu Yuliantoro; Nurasih Romadloni; Heriyanto Kandati (RADJA PUBLIKA, 2024)
This article aims to describe the pattern of terrorism prevention with the collaboration of Intelligence-Led Policing and Predictive Policing in the South Sumatra region. Until now, there has only been one terrorist attack in South Sumatra, namely the shooting of a Christian junior high school teacher in Palembang City in 2008 with the motive that the teacher often insulted students who wore headscarves at his school. So far, the South Sumatra Regional Police have succeeded in preventing terrorist attacks, as evidenced by several arrests made before the terrorist attacks in 2017, 2018 and 2020. However, the concept of preventing terrorist attacks has not been carried out systematically by the Intelligence Function at the South Sumatra Regional Police. The prevention carried out has not been systematically through the intelligence-led policing process so that it can predict the potential threat of terrorist attacks. So far, prevention patterns have been carried out by the intelligence of Densus 88 Polri. The involvement of the South Sumatra Regional Police Intelligence is still minimal in efforts to prevent terrorism.